KS0- and (anti-)λ-hadron correlations in pp collisions at √s=13 TeV - Acharya, Shreyasi; Angelov, Venelin; Arslandok, Mesut; Berdnikova, Anastasia; Bergmann, Luisa; Danisch, Meike; Feuillard, Victor; Glässel, Peter; Kim, Jiyoung; Kim, Minjung; Köhler, Markus Konrad; Kroesen, Martin; et al. (The European physical journal. C, Particles and fields, 2021)
Two-particle Azimuthal correlations are measured with the ALICE apparatus in pp collisions at $$\sqrt{s} = 13$$TeV to explore strangeness- and multiplicity-related effects in the fragmentation of jets and the transition regime between bulk and hard production, probed with the condition that a strange meson ($$K_S^{0}$$) or baryon ($$Λ $$) with transverse momentum $$p_{\mathrm T} >3$$GeV/$$c$$is produced. Azimuthal correlations between kaons or $$Λ $$hyperons with other hadrons are presented at midrapidity for a broad range of the trigger ($$3< p_T^trigg < 20$$GeV/$$c$$) and associated particle $$p_{\mathrm T}$$(1 GeV/$$c$$$$< p_T^assoc < p_T^trigg $$), for minimum-bias events and as a function of the event multiplicity. The near- and away-side peak yields are compared for the case of either $$K_S^{0}$$or $$Λ $$($${\overline{Λ }}$$) being the trigger particle with that of inclusive hadrons (a sample dominated by pions). In addition, the measurements are compared with predictions from PYTHIA 8 and EPOS LHC event generators.